Toxic effects of the Emamectin Benzoate exposure on cultured human bronchial epithelial (16HBE) cells. (February 2020) - Niu, Chenguang; Wang, Chunli; Wu, Guangyao; Yang, Jingnan; Wen, Yanan; Meng, Shuangshuang; Lin, Xuhong; Pang, Xiaobin; An, Lei
Abstract: Pesticides pollution has caused serious environmental problems in recent years, and mounting evidence has shown that more and more insecticides have serious risk in human health. Emamectin Benzoate formally regarded as a highly safety insecticide based on its exclusive targets, but the cytotoxicity to human lung was ignored for a long time. In the present study, bioassay experiments were used to assess the toxicity of the Emamectin Benzoatein on human non-target cells including cell viability assay, DNA damage assay, flow cytometer assay and western blotting assay. The results indicated that Emamectin Benzoatecan cause the inhibition of the proliferation, cytochrome c release, activation of caspase-3/9 and increase Bax/Bcl-2 ratio, which means it induced the cytotoxicity on 16HBE cells associated with the mitochondrial apoptosis. Besides, the DNA damge caused by the Emamectin Benzoate suggest it has a potential genotoxic effect on human lung cells. Graphical abstract: Image 105289 Highlights: Emamectin benzoate exposure inhibited the viability of 16HBE cells. Emamectin benzoate exposure induced DNA damage and apoptosis. Emamectin benzoate generate reacted oxygen species. Emamectin benzoate-induced apoptosis related to mitochondrial pathway. Emamectin benzoate has risks to human health.